Strategi Daya Saing Untuk Meningkatkan Omset Penjualan Umkm Warung Sembako Mak De Dalam Perspektif Ekonomi Syari’ah - Shella Perdana Putri; Muhammad Apis Daulay; Taufik Hidayat (Journal of Islamic Economic and Law (JIEL), 2025)
Warung Sembako Mak De experienced a decline in turnover due to competition, less strategic location, and conventional marketing strategies, so it needs to be analyzed from a sharia economic perspective. This study aims to analyze the competitiveness strategy in increasing the sales turnover of the Mak De Grocery Store UMKM in Sungai Pasir Putih Village, Kelayang District, Indragiri Hulu Regency, from a sharia economic perspective. This study was motivated by a significant decline in sales turnover in recent years, which was caused by the increasing number of competitors, less strategic business locations, and less than optimal implementation of marketing strategies and business management. The research method used was descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The subjects of the study were the owners of the Mak De grocery store. Data analysis was carried out using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that the competitiveness strategy applied was still limited to conventional services, competitive prices, and word of mouth promotion. There has been no significant use of digital technology or product innovation. Sales turnover tends to decrease from year to year. However, business actors have tried to apply sharia economic principles such as honesty, trustworthiness, and seeking blessings in business. This study recommends the need for innovation in marketing strategies, the use of simple technology, and the strengthening of Islamic economic principles more comprehensively so that UMKM can develop sustainably.